AN EMPIRICAL STUDY ON IMPACT OF INFLATION RATE ON STOCK MARKET PERFORMANCE IN INDIA - Swarnalatha, Mrs. K.; Sridhar, Dr. P.; Krishnmohan, K.V.S. (The journal of contemporary issues in business and government, 2022)
BSE index SENSEX and BSE index NIFTY are the major indexes in India which is a measuring indicator of the economic development of India. The Inflation rate is one of the macroeconomic factors which influence the stock market directly or indirectly. Any country tries to make an economic policy to stabilize the inflation rate of their economy. The relationship between the stock market and the Inflation of a country has been a captivating concept for any policy maker and the researcher. The present study made an attempt to understand the relationship between inflation and stock market returns in India. The data from 2010 to 2022 is taken for the analysis.